ANALISIS KEBIJAKAN PENERAPAN SURAT PERNYATAAN TANGGUNG JAWAB MUTLAK (SPTJM) SEBAGAI DOKUMEN ADMINISTRASI PENCATATAN PERKAWINAN/PERCERAIAN TIDAK TERCATAT DALAM PERSPEKTIF MASLAHAT SOSIAL: Policy Analysis on the Implementation of Absolute Responsibility Statement (SPTJM) as an Administrative Documents on Unregistered Marriage/Divorce in a Social Profits Perspective - Anggelina Hariyanti; M. Hasan Busyairi; Nurhasanah Nurhasanah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Marriages should be registered according to Law Number 1/1974. Although failure to register does not invalidate the validity of the marriage, it makes it difficult to obtain administration services. The government then facilitated it with an affirmative policy, Permendagri Number: 109 of 2019, but it still caused polemics in society. Novelty: The aim of this research is to analyze the policy of implementing SPTJM for unregistered marriages/divorces in the inclusion of marital status on family cards from a social benefit perspective. Methods: This research uses a descriptive qualitative method with a normative juridical approach. Data was obtained from statutory regulations and research results as primary data and secondary data. Results and Conclusion: Results and conclusions: The use of SPTJM provides two perspectives, first, making it easier for citizens to obtain administration services; secondly, it provides an opportunity for violations of related laws and regulations and abuse of the noble institution of marriage.